ANALISA TRANSISTOR BJT BERBASIS SIMULASI MENGGUNAKAN APLIKASI PROTEUS SEBAGAI MEDIA PENUNJANG PEMBELAJARAN - Sunardi; Muhamad Sulaiman (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
BJT Transistor (Bipolar Jungtion Transistor) is a type of active electronic component that has 3 legs, the third of which is a very unique electronic component, the transistor has many advantages. Transistors are small components that have quite unique capabilities in electronic circuits. Therefore, this experiment was carried out in order to find out the basic configuration characteristics of Bipolar Junction Transistor Common Base, Common Emitter and Common Collector. The research method that the author uses is the one where this method is used for Simulation-Based BJT Transistor Analysis Using the Proteus Application as a Learning Support Media. So that the basic electronics learning method can understand the characteristics of transistors, which can make it easier for students to carry out practical work in the basic electronics laboratory in the bipolar junction transistor (BJT) transistor module.